Simple analytical expression for vector hypernuclear asymmetry in nonmesonic decay ofΛ 5He andΛ 12C - Barbero, César; Krmpotić, Francisco; Galeão, Alfredo P. [UNESP] (FapUNIFESP (SciELO), 2006)
We present general explicit expressions for a shell-model calculation of the vector hypernuclear parameter in nonmesonic weak decay. We use a widely accepted effective coupling Hamiltonian involving the exchange of the complete pseudoscalar and vector meson octets (π, η, K, ρ, ω, K*). In contrast to the approximated formula widely used in the literature, we correctly treat the contribution of transitions originated from single-proton states beyond the s-shell. Exact and simple analytical expressions are obtained for the particular cases of Λ 5He and Λ 12C, within the one-pion-exchange model. Numerical computations of the asymmetry parameter, aΛ, are presented. Our results show a qualitative agreement with other theoretical estimates but also a contradiction with recent experimental determinations. Our simple analytical formulas provide a guide in searching the origin of such discrepancies, and they will be useful for helping to solve the hypernuclear weak decay puzzle.
Keywords: Asymmetry parameter; Hypernuclear decay; One-meson-exchange model